Tolerance of immobilized yeast cells in imidazolium-based ionic liquids - Yang, Zhong-Hua (Array, 2009)
Summary: Ionic liquids (ILs) are considered as another ’green solvent’, after the supercritical carbon dioxide. They are a promising reaction medium for biocatalysis process. The tolerance of active cells in hydrophobic imidazolium-based ILs (1-R-3-methylimidazolium hexafluorophosphate, [RMim][PF6]) has been studied in this work. Calcium-alginate-entrapped baker’s yeast has been chosen as the model of living cells. The results show that this kind of ILs possess a certain degree of biocompatibility. The tolerance of yeast cells to the ILs decreases with the increase of the R chain length of these ILs. The experiment indicated that 1-butyl-3-methylimidazolium hexafluorophosphate ([BMim][PF6]) possessed excellent biocompatibility compared to the other imidazolium-based ILs. The moisture content in the ILs was the key factor that affected the tolerance. The activity retention of yeast cells pretreated with [BMim][PF6] saturated with water and aqueous [BMim][PF6] biphasic system was about 70 %, but it was only 50 % with the anhydrous [BMim][PF6]. Although the yeast cells were pretreated with [BMim][PF6] for 24 h, the activity retention was up to 45 %. The yeast cells had around 50 % activity after being pretreated 4 times with [BMim][PF6]. This shows that the water immiscible ILs possess good biocompatibility, and they are suitable for application as the reaction medium catalyzed by living cells